Increasing TCP friendliness by implementing simple adaptive congestion control framework in wireless network - Elangkovan, Sri Ganesh (2018)
As new connection innovations and sub-systems multiply and develop an extensive number of TCP variations have been produced for various kinds of the system situations. They can prompt significant execution picks up by exploiting neighborhood qualities of the particular arrange. Be that as it may, these TCP variations couldn't be consequently picked by the bring down system conditions. In this experiment, we create an congestion control mechanism ACCF, a versatile congestion based control structure, which dismiss consequently progress amid current congestion control algorithm components as indicated by the difference in the system status. At that point we play out a straightforward usage of ACCF over the systems with high data transmission defer item. It can shift the congestion control mechanism methods amid the deferral centered ones then the misfortune centered ones as indicated by the system position.. For the reenactment measures, the trial comes about demonstrate that the execution of ACCF is essentially enhanced when contrasted with other best in class calculations in term of throughput, reasonableness and TCP-Friendliness.